2019
DOI: 10.33772/jitro.v6i2.5936
|View full text |Cite
|
Sign up to set email alerts
|

Viabilitas Spermatozoa Sapi Bali Menggunakan Pengencer Andromed dengan Penambahan Konsentrasi Sari Wortel yang Berbeda

Abstract: ABSTRAK                                                                        Penggunaan andromed pada waktu tertentu sulit untuk didapatkan sehingga perlu alternatif lain untuk mengurangi penggunaan andromed. Tujuan penelitian untuk mengevaluasi pengaruh sari wortel sebagai bahan pengencer mengurangi penggunaan pengencer andromed pada semen sapi bali terhadap kualitas spermatozoa sapi bali. Penelitian ini menggunakan semen sapi bali dari Balai Inseminasi Buatan Tuah Sakato, Payakumbuh. Rancangan yang digunak… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 5 publications
0
2
0
1
Order By: Relevance
“…Sperm abnormality values in Optixcell ® and Andromed ® diluent were the same, below 20%. Yendraliza et al (2019) showed abnormalities of frozen semen of Bali cattle in Andromed ® diluent, with various percentages of carrot juice after thawing, to be around 5.17% to 10.50%. Utami and Tophianong (2014) showed that the highest abnormality of sperm thawed in water at 8 o C and 37 o C was 20% and 23%.…”
Section: Intact Plasma Membrane (Ipm) Simmental Frozenmentioning
confidence: 99%
“…Sperm abnormality values in Optixcell ® and Andromed ® diluent were the same, below 20%. Yendraliza et al (2019) showed abnormalities of frozen semen of Bali cattle in Andromed ® diluent, with various percentages of carrot juice after thawing, to be around 5.17% to 10.50%. Utami and Tophianong (2014) showed that the highest abnormality of sperm thawed in water at 8 o C and 37 o C was 20% and 23%.…”
Section: Intact Plasma Membrane (Ipm) Simmental Frozenmentioning
confidence: 99%
“…Penampilan kambing PE mirip dengan kambing etawa namun ukurannya lebih kecil dan lebih adaptif terhadap lingkungan lokal Indonesia. Kambing ini merupakan jenis ternak dwiguna, yaitu mampu memproduksi susu dan daging (Yendraliza et al, 2016).…”
Section: Pendahuluanunclassified
“…An intact plasma membrane test was performed using a hypoosmotic sewer solution (HOS) test [8]. HOS solution was prepared by mixing 2.70 g of fructose, and 0.47 g of sodium citrate with 100 ml of aquabidest and homogenized.…”
Section: Intact Plasma Membrane (Ipm)mentioning
confidence: 99%